Labour relations in Norway - Løken, Espen; Stokke, Torgeir Aarvaag (Oslo, 2009)
"Labour relations constitute an important part of the Norwegian social model, characterised by strong employers’ and workers’ organisations and by close cooperation between the government, employers’ associations and trade unions, as well as by strong co-determination and participation at company level. This report gives an up to date inter-disciplinary picture by describing the main institutional frameworks and social actors, at both national and enterprise level, within Norwegian working life. The report consists of seven parts; a general introduction, legal framework, the organisations, collective bargaining, tripartite concertation, relations at company level, and Norway and the European Union."